بيوع الآجال وتطبيقاتها المعاصرة البنك الإسلامي للتنمية وبنك إسلام ماليزيا نموذجان : دراسة تحليلية مقارنة - إبن محمد، عبد الله (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2007)
Differed sales are considered lawful externally, due to the contract principles and conditions contained therein. Generally, the objective is not the essence or the reality pertaining to it but people employ it intentionally as a means of practicing usury based on the outward principles. These kinds of transactions are of various forms and as a result, Muslim scholars have great differences over their legal aspects. These transactions have dominated all aspects of business in this contemporary world to the extent that almost none can do without it due to the contemporary need of business exercise in various Islamic organizations. Regarding the significance of these transactions as being applied in all spheres of life on the one hand, and its harm as means of usury on the other, thus, there is a comprehensive need for a critical Islamic study pertaining to these kinds of transactions. The study’s theoretical dimension comprises various opinions from different Muslim scholars whereas the practical aspect deals with whether the contemporary applications by the Islamic Development Bank and Bank Islam Malaysia are inconformity with the Islamic Shari'ah.